INVENTORY OF RED CHILI (CAPSICUM ANNUM L.) PLANT DISEASES IN PAKEM DISTRICT, SLEMAN REGENCY - Ulilalbab, Azizah Ridha; Ajri, Miftahul; Poerwanto, Mofit Eko; Wicaksono, Danar (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
Red chili is cultivated practically everywhere and plays a crucial role in Indonesian culture, economy, and cuisine. Plant diseases have been the main factor driving the country’s yield reduction of red chili. This research was conducted to observe chili plant diseases in Hargobinangun Subdistrict, Pakem District, Sleman, Yogyakarta. Chili variety Twist-42 was planted in the area. The Twist-42 variety is a local variety that is well adapted in the middle plains between 450 – 650 masl (meters above sea level) and is a good variety in both the dry and rainy seasons. There were 360 red chili plants as samples. The diseases found are Yellow leaf curl disease, Anthracnose, Ralstonia wilt, and Root knot nematode (Meloidogyne spp.).